1990
DOI: 10.1128/mcb.10.6.2485
|View full text |Cite
|
Sign up to set email alerts
|

RAD10, an excision repair gene of Saccharomyces cerevisiae, is involved in the RAD1 pathway of mitotic recombination.

Abstract: The RADIO gene of Saccharomyces cerevisiae is required for the incision step of excision repair of UV-damaged DNA. We show that the RADIO gene is also required for mitotic recombination. The radlOA mutation lowered the rate of intrachromosomal recombination of a his3 duplication in which one his3 allele has a deletion at the 3' end and the other his3 allele has a deletion at the 5' end (his3A3' his3A5'). The rate of formation of HIS3+ recombinants in the radlOA mutant was not affected by the radlA mutation but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
82
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(84 citation statements)
references
References 43 publications
2
82
0
Order By: Relevance
“…Thus these results rule out the theoretical possibility raised by these and other remarkable observations with respect to the ERCC3 gene in the yeast and Drosophila systems, namely that the ERCC3 -NER connection could be indirect, i.e. ERCC3 might control the expression of one or more (real) NER genes without being involved itself in this process (Gulyas and Donahue, 1992;Mounkes et al, 1992;Schaeffer et al, 1993 (Schiestl and Prakash, 1990;Bailly et al, 1992;Bardwell et al, 1992;Biggerstaff et al, 1993;van Vuuren et al, 1993). Using the in vitro NER assay Wood and coworkers have shown that the replication factors PCNA and HSSB (RPA) also participate in the post-incision stages of the NER reaction (Coverley et al, 1992;Shivji et al, 1992) Serizawa et al, 1993a,b) and a helicase activity (Schaeffer et al, 1993 (Gerard et al, 1991).…”
Section: Discussionmentioning
confidence: 40%
“…Thus these results rule out the theoretical possibility raised by these and other remarkable observations with respect to the ERCC3 gene in the yeast and Drosophila systems, namely that the ERCC3 -NER connection could be indirect, i.e. ERCC3 might control the expression of one or more (real) NER genes without being involved itself in this process (Gulyas and Donahue, 1992;Mounkes et al, 1992;Schaeffer et al, 1993 (Schiestl and Prakash, 1990;Bailly et al, 1992;Bardwell et al, 1992;Biggerstaff et al, 1993;van Vuuren et al, 1993). Using the in vitro NER assay Wood and coworkers have shown that the replication factors PCNA and HSSB (RPA) also participate in the post-incision stages of the NER reaction (Coverley et al, 1992;Shivji et al, 1992) Serizawa et al, 1993a,b) and a helicase activity (Schaeffer et al, 1993 (Gerard et al, 1991).…”
Section: Discussionmentioning
confidence: 40%
“…Because it is likely that the ends of the resected DSB will not be complementary, virtually every SSA event will almost certainly require a flap-processing step. The 3 0 -protruding end removal in D-loop and SSA intermediates has been extensively studied (Schiestl and Prakash 1990;Fishman-Lobell et al 1992;Tomkinson et al 1993). The process appears to depend primarily on the ScMsh2-ScMsh3 heterodimer, which both recognizes and stabilizes flap-containing heteroduplexes Sugawara et al 1997;Kearney et al 2001).…”
Section: The Mmr System In Heterologous Flap Processingmentioning
confidence: 99%
“…However, other studies of direct repeat recombination have shown that deletions commonly occur without generating the circular product predicted to form through a crossover event (Fishman-Lobell et al, 1992). Moreover, many deletion events are dependent on RAD1 and RAD10 (Klein, 1988;Schiestl and Prakash, 1990;Ivanov and Haber, 1995). The Rad1 and Rad10 proteins form a structurespecific endonuclease that generates 5′ single-stranded ends (Siede et al, 1993).…”
Section: Introductionmentioning
confidence: 99%